Enterprise software and service innovation: Standardization versus customization - Benjamin Engelstätter; Miruna Sarbu (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
This paper analyzes the relationship between service innovation and different types of enterprise software systems, i.e. standardized enterprise software designed to fit one certain business sector and enterprise software specifically customized for a single firm. Using firm-level data of a survey among ICT service providers and knowledge-intensive service providers in Germany, this is the first paper empirically analyzing whether both types of enterprise software foster innovation in the service sector. The analysis is based on a knowledge production function. The results reveal that there is no relationship between sector specific enterprise software and innovation activity while customized enterprise software is possibly related to the probability of service innovation. The results stay robust if former innovation activity and general openness to new technologies are controlled for.
Keywords: L10; M20; O31; 330; enterprise systems; service innovation; customized enterprise software; sector specific enterprise software; Dienstleistung; Innovation; EDV-Dienstleistung; Unternehmensdienstleistung; Computergestütztes Verfahren; Betriebliches Informationssystem; PC-Software; Schätzung; Deutschland